The Implementation Of Viewboard Of The Head Of Department As A Media For Student Information Is Worth Doing Final Research - Aini, Qurotul; Sunarya, Po Abas; Bein, Adrian Sean; nursaputri, Pipit (Pandawan Sejahtera Indonesia, 2019)
Submission of information is a very important thing that is owned by a system. The system that is made very well will be able to convey good and clear information to its users so that it can communicate well. The more rapid technology has been used by several educational institutions, especially universities, to support the existing learning system. For students who have fulfilled the requirements for conducting final research, it is appropriate to declare to carry out the final research. But the head of the department is still required to come to campus to declare that the student is eligible or not to do the final research. Therefore we need a system that can provide convenience for the Head of Department to declare that students are eligible to do final research that can be accessed online so that it can be accessed anywhere and anytime by the Head of Department and does not need to come to campus because the system still uses local networks. In order to provide convenience and effectiveness for the Head of Department to check and provide eligibility for students eligible for final research which then leads to the maximum service to students. In conducting research research methods used in this study namely observation, interviews and literature study In the process of developing the system the writer uses 4 stages, namely problem identification, planning, designing prototypes and reviewing prototypes. Evidenced by the viewboard of the head of the department of service to students, it was very well fulfilled.